2014
DOI: 10.1002/jor.22745
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cdk11 in osteosarcoma cells using the CRISPR‐cas9 system

Abstract: Osteosarcoma is the most common type primary malignant tumor of bone. Patients with regional osteosarcoma are routinely treated with surgery and chemotherapy. In addition, many patients with metastatic or recurrent osteosarcoma show poor prognosis with current chemotherapy agents. Therefore, it is important to improve the general condition and the overall survival rate of patients with osteosarcoma by identifying novel therapeutic strategies. Recent studies have revealed that CDK11 is essential in osteosarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 49 publications
5
42
0
3
Order By: Relevance
“…CDK11 may also play a role in cancer cell migration and invasion, as the migration and invasion activities were significantly reduced in CRISPR-Cas9 CDK11 knockout cancer cells (42). Knockdown of CDK11 by CRISPR-based RNAi technology also showed growth-inhibiting effects in mammalian tuberous sclerosis complex 2 (TSC2)-deficient cell lines, including in human tumor-derived acute myeloid leukemia (AML) cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…CDK11 may also play a role in cancer cell migration and invasion, as the migration and invasion activities were significantly reduced in CRISPR-Cas9 CDK11 knockout cancer cells (42). Knockdown of CDK11 by CRISPR-based RNAi technology also showed growth-inhibiting effects in mammalian tuberous sclerosis complex 2 (TSC2)-deficient cell lines, including in human tumor-derived acute myeloid leukemia (AML) cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…En líneas celulares de osteosarcoma, el silenciamiento estable de Quinasa dependiente de ciclina (Cdk11), con CRISPR/Cas aumenta la muerte celular, disminuye la migración y reduce la invasión por células malignas (51) ; en otros experimentos, se corrigieron el gen Fah para la tirosinemia43 y el gen Dmd para la distrofia a muscular de Duchenne (52) y en células madre intestinales de pacientes con fibrosis quística, se logró la modificación del receptor de membrana CFTR (Cystic Fibrosis transmenbrane conductance regulator). Estas evidencias confirman que CRISPR/Cas es un sistema viable y eficaz, aplicable en modelos de animales adultos, para el desarrollo de terapias génicas (52) .…”
Section: Interpretación De La Información Codificada En El Adn Bacterunclassified
“…Several studies have revealed that CDK11 is essential in cancer, including in sarcoma cell growth and survival [21, 23, 33, 71, 86]. Our previous study identified that CDK11 is critical for the growth and proliferation of liposarcoma cells, suggesting that CDK11 may be a promising therapeutic target for treatment of liposarcoma patients [33].…”
Section: Potential Applications Of Crispr-cas9 In Sarcomamentioning
confidence: 99%
“…Our previous study identified that CDK11 is critical for the growth and proliferation of liposarcoma cells, suggesting that CDK11 may be a promising therapeutic target for treatment of liposarcoma patients [33]. Recently, CRISPR-Cas9 was applied to determine the effect of targeting endogenous CDK11 at the DNA level in osteosarcoma cell lines [23]. Furthermore, the migration and invasion activity was markedly reduced by CDK11 knockout, indicating that CDK11 maybe a novel therapeutic target for osteosarcoma [23].…”
Section: Potential Applications Of Crispr-cas9 In Sarcomamentioning
confidence: 99%
See 1 more Smart Citation